Imidazolium‐functionalized SBA‐15 type silica: efficient organocatalysts for Henry and cycloaddition reactions. (11th April 2013) - Motos‐Pérez, Blanca; Roeser, Jérôme; Thomas, Arne; Hesemann, Peter
<x xml:space="preserve">Abstract</x> We report the synthesis of mesoporous SBA‐15 type silica bearing ionic imidazolium substructures. Surface functionalization was achieved via post‐synthesis grafting reactions using bis‐silylated imidazolium precursors onto a mesoporous SBA‐15 type silica support. The grafting reactions were monitored via solid‐state NMR spectroscopy, nitrogen sorption, transmission electron microscopy and thermogravimetry. Post‐synthesis grafting is the most convenient way to achieve highly stable functionalized solids displaying excellent accessibility of the immobilized functional groups combined with high chemical stability. The solids obtained via post‐synthesis grafting reactions appeared as highly efficient and reusable heterogeneous organocatalysts for Henry reactions and the cycloadditions of CO2 to epichlorohydrin. Copyright © 2013 John Wiley & Sons, Ltd.